PIG MEAT MARKET IN SELECTED EU COUNTRIES UNDER THE CONDITIONS OF ECONOMIC INTEGRATION: A COMPARATIVE ANALYSIS OF OLD AND NEW MEMBER STATES - Stępień, Sebastian; POLCYN, Jan (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 18 (2016): Annales Universitatis Apulensis Series Oeconomica, 2016)
The objective of the paper is to present the changes that have taken place in the EU pig meat market under the conditions of economic integration. The study aims to evaluate the gains and losses arising from EU accession for the Central and Eastern European countries and the socalled “old” EU countries. The authors adopted the hypothesis that those gains and losses are not uniformly distributed, - the EU-15 countries benefit, while the new member states lose out from the changes. The analysis covered five EU-15 member states, i.e. Germany, Spain, France, Denmark and the Netherlands, and four new EU members, i.e. Poland, Romania, Hungary and the Czech Republic. The material scope of the paper includes the changes in supply (pig stock and production), prices and foreign trade, while the temporal scope encompasses the period from 1995 to 2015. An evaluation of the trends in the pig meat market with respect to the changes in supply, prices, and foreign trade reveals that the “old” EU countries benefitted from the accession of new member states to the European Union.